Design of environmental friendly hybrid electric vehicle - Ullah, Mohammad Habib; Gunawan, Teddy Surya; Sharif, Md. Raihan; Muhida, Riza (2012)
Hybrid electric vehicles (HEVs) powered by electric machines and an internal combustion engine (ICE) are a promising mean of reducing emissions and fuel consumption without compromising vehicle functionality and driving performances. This paper presents the design of an environmental friendly hybrid car that feature the gasoline engine and batteries pack. The fuel consumption benefited by hybridization are benchmarked to conventional Gasoline and Diesel fueled vehicles. The relationship between fuel consumption and vehicle weight is investigated for Gasoline as well as for Diesel fueled vehicles. Although the automobile manufacturers have reduced the greenhouse gases such as hydro-carbons, carbon monoxide, carbon dioxide, etc., from the vehicle, they cannot produce a zero-emission vehicle unless they produce an electric vehicle (EV). An electric vehicle is an emission free, environmental friendly vehicle. The proposed design of HEV intelligently gets around the individual problems associated with the gasoline engine and the electric vehicle. It diminishes the production of emissions and the use of fuel. The problem of batteries for the electric vehicle is conquered. An HEV charges itself; it never has to be plugged in. When it does not provide power, the motor can run as a generator to transfer energy from regenerative braking and from the gasoline engine to the batteries.